A institucionalização parcial da política de habitação em Abaetetuba/PA: reflexos sociais e assentamentos precários - PINTO, Nilma Batista (2023)
This research was possible from the insertion in the Field of Compulsory Supervised Internship I, II and III of the Bachelor's Degree in Social Work in the Abaetetuba Housing Space. This space has been developing the Housing Policy in the municipality since 2009 through the execution of the Housing Programs My House My Urban and Rural Life, Housing of Social Interest and Housing Check, and aims at the equation of the housing deficit in the municipality and the promotion of better housing conditions for residents. Based on this premise, this study aims to describe how the Housing Policy is instituted in Abaetetuba, as well as to point out the situational situation of housing, precarious settlements, their social effects and spatial implications in the municipality. The aim was to analyze the advances obtained and the difficulties faced for the institutionalization of the housing policy in the municipality, the implemented Housing Programs and if there was an equation in the housing deficit of the municipality since the implementation of this policy in the municipality. To achieve these objectives, the methodology of qualitative research was used, through a survey of bibliographic references and documentary research in the Housing Space of the municipality. There were also interviews with municipal management, technical staff and the Housing Space Coordination of Abaetetuba. As a result of the research it was noticed that the housing policy has developed in a fragmentary way since its institutionalization in the municipality and its effectiveness has not reached the objectives and general principles of the national housing policy, causing social reflexes, segregation, irregular occupations, absence urban mobility, environmental degradation and improvisational urban development. There is no Municipal Housing Council and no Municipal Housing Plan. It should be noted that in addition to the partial institutionalization of housing policy in the municipality, the professionals involved face other setbacks in its effectiveness, such as the precariousness of work, lack of materials, equipment and the minimum staff that compose the municipality's Housing Space. It is emphasized that the housing issue is not a priority of the previous ones and the current municipal management.